Reduced relative volume in motor and attention regions in developmental coordination disorder: A voxel-based morphometry study. - Reynolds, J.; Licari, M.; Reid, S.; Elliott, Catherine; Winsor, A.; Bynevelt, M.; Billington, J. (2017)
Background and objectives: Developmental coordination disorder (DCD) is a prevalent childhood movement disorder, impacting the ability to perform movement skills at an age appropriate level. Although differences in grey matter (GM) volumes have been found in related developmental disorders, no such evidence has been linked with DCD to date. This cross-sectional study assessed structural brain differences in children with and without DCD. Methods: High-resolution structural images were acquired from 44 children aged 7.8–12 years, including 22 children with DCD (≤16th percentile on MABC-2; no ADHD/ASD), and 22 typically developing controls (≥20th percentile on MABC-2). Structural voxel-based morphology analysis was performed to determine group differences in focal GM volumes. Results: Children with DCD were found to have significant, large, right lateralised reductions in grey matter volume in the medial and middle frontal, and superior frontal gyri compared to controls. The addition of motor proficiency as a covariate explained the between-group GM volume differences, suggesting that GM volumes in motor regions are reflective of the level of motor proficiency. A positive correlation between motor proficiency and relative GM volume was also identified in the left posterior cingulate and precuneus. Conclusions: GM volume reductions in premotor frontal regions may underlie the motor difficulties characteristic of DCD. It is possible that intervention approaches targeting motor planning, attention, and executive functioning processes associated with the regions of reduced GM volume may result in functional improvements in children with DCD.